ナンキョク チイキ ノ チキュウ カガクテキ ケンキュウ ト チガク ニ オケル ジャッカン ノ カダイ ニ カンスル オボエガキ - 吉田, 栄夫; ヨシダ, ヨシオ; YOSHIDA, Yoshio (国立極地研究所, 1977)
P(論文) 第2回南極地球化学シンポジウムに際して,地球科学の隣接分野からの地球化学的研究への提言として,次のコメントを行った.まず,南極氷床の発達と変動に関係すると考えられる諸事象を,時間的尺度を基準にして区分する.時間的尺度の階級は,10^<-1>～10^1 (年), 10^1～10^3, 10^3～10^5, 10^5～10^6, 10^6～10^7とした.この区分された氷床変動に関連する事象と地球化学的研究の関係について簡単に言及し,この区分が,地球化学調査・考察の枠組の一つとして利用され得ることを述べた.さらにこれと関連して,南極の"氷期"もしくは氷床の拡大・縮小と,これに影響を及ぼし,また及ぼされる諸要素を,資料的にきわめて不充分な段階ではあるが,今後検討さるべきものとして,かりに編年的に整理し提示した. On the occasion of the Symposium on Antarctic Geochemistry, the following comment is made on geochemical research, as a suggestion from neighboring fields of earth sciences. The arrangement of phenomena related to the evolution and fluctuation of the Antarctic Ice Sheet, on the basis of time-scale, is proposed as a kind of framework for geochemical investigation in Antarctica. The classification of time-scale may fall into five ranks, i.e. 10^<-1>～10^1 (year), 10^1～10^3, 10^3～10^5, 10^5～10^6, 10^6～10^7. Brief discussion is given on the relationship between phenomena concerning the fluctuation of the ice sheet and the geochemical investigation or method. In this connexion, a speculative chronological correlation of glacial events in Antarctica is tabulated based on several sources including the author's own data. departmental bulletin paper